Design and Implementation of Chatbot Pancasila for Teaching Pancasila and Character Building for University’s Students - Karina Dwinovera Mulia; Widodo Budiharto; Heri Ngarianto; Frederikus Fios (International Journal of Computer Science and Humanitarian AI, 2025)
In the modern era, where global influences are rapidly shaping young minds, the need to maintain strong national identity and moral values is more crucial than ever. For Indonesian students, Pancasila education and character building play a central role in developing not only academic competence but also personal integrity and social responsibility.  The design approach involved analyzing student needs, integrating Pancasila-based content, as well as applying automated learning algorithms so that the chatbot can provide answers that match the context of the conversation especially Character-Building Pancasila topics. This Pancasila Character Building Chatbot is designed with Natural Language Processing (NLP) technology to provide creative, interactive, and interesting learning experiences that are easily understood by students. Implementation is done through a digital platform that allows students to interact in real-time in understanding the values of Pancasila, such as divinity, humanity, unity, democracy, and social justice. Furthermore, this innovation aims to bridge the gap between traditional moral education and modern digital learning methods. By utilizing artificial intelligence, the chatbot can adapt to different learning styles and provide personalized feedback to each student. It is hoped that the presence of Chatbot Character Building Pancasila can increase the enthusiasm for learning and curiosity of students so that learning character building Pancasila is more creative and interesting for students in university classrooms.